THE CONCEPT OF INNER PEACE AS A VALUE IN ISLAMIC EDUCATION: AN ANALYSIS OF THE PREACHING OF USTADZ ADI HIDAYAT AND USTADZ ABDUL SOMAD - Aliah, Fatimah; Silviana, Nadia; Pratama , M. Andri; Sari , Sella Mustika; Satra, Alihan (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study aims to examine the concept of inner peace as a value of Islamic education through the analysis of the sermons of Ustadz Adi Hidayat and Ustadz Abdul Somad. The research employs a descriptive method with a qualitative approach. The findings reveal that both preachers emphasize the importance of inner peace as part of the formation of a Muslim's character and spirituality. Ustadz Abdul Somad highlights five core practices for achieving inner peace: dhikr (remembrance of God), wudhu (ablution), prayer, reading the Qur’an, and socializing with pious people. Meanwhile, Ustadz Adi Hidayat underscores values such as gratitude, the meaning of the adhan (call to prayer) as a call toward falah (true success), and prayer as the main instrument for achieving inner tranquility. Both agree that inner peace is not merely the result of ritual acts but a product of deep spiritual closeness to Allah SWT. This concept holds strategic value in Islamic education as it serves as a foundation for developing individuals who are calm, grateful, and spiritually grounded. The study concludes that the sermons of these two figures offer a significant contribution to integrating inner peace as an essential value in Islamic education. Penelitian ini bertujuan untuk mengkaji konsep ketenangan jiwa sebagai nilai pendidikan Islam melalui analisis dakwah Ustadz Adi Hidayat dan Ustadz Abdul Somad. Metode yang digunakan adalah deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa kedua pendakwah menekankan pentingnya ketenangan jiwa sebagai bagian dari pembentukan karakter dan spiritualitas seorang Muslim. Ustadz Abdul Somad menguraikan lima amalan utama untuk mencapai ketenangan jiwa, yaitu dzikir, wudhu, shalat, membaca Al-Qur’an, dan berinteraksi dengan orang-orang saleh. Sementara itu, Ustadz Adi Hidayat menekankan nilai-nilai seperti rasa syukur, pemaknaan adzan sebagai panggilan menuju falah (kesuksesan sejati), serta shalat sebagai instrumen utama untuk mencapai kedamaian batin. Keduanya sepakat bahwa ketenangan jiwa bukan sekadar hasil dari praktik ritual, melainkan merupakan buah dari kedekatan spiritual yang mendalam dengan Allah SWT. Konsep ini memiliki nilai strategis dalam pendidikan Islam karena dapat menjadi dasar dalam membentuk pribadi yang tenang, bersyukur, dan berorientasi pada nilai-nilai ketuhanan. Penelitian ini menyimpulkan bahwa dakwah kedua tokoh tersebut memberikan kontribusi penting dalam mengintegrasikan ketenangan jiwa sebagai nilai esensial dalam pendidikan Islam.